Oxidation-induced destabilization of polymorphic α-synuclein fibrils: insights from molecular dynamics - Akramov, Tohir; Marimuthu, Parthiban; Makhkamov, Mukhriddin; Shahzad, Aamir; Mashalov, Rasulbek; Razzokov, Jamoliddin (Frontiers in Physics, 2025)
The build-up of α-Synuclein (αSyn) fibrils is a key feature of Parkinson’s disease (PD) and other synucleinopathies. While oxidative stress has been implicated in αSyn aggregation, its precise effects on fibril stability remain unclear. In this study, we use molecular dynamics (MD) simulations and enhanced sampling techniques to investigate the impact of oxidation-induced modifications on the conformational stability of αSyn polymorph fibrils. Three oxidation models (OX1, OX2, and OX3), featuring progressively increased oxidation levels, were generated and compared to the native fibril structure. Key structural analyses, including root mean square deviation (RMSD), secondary structure content, solvent-accessible surface area (SASA), and hydrogen bonding, reveal that oxidation induces significant destabilization of αSyn polymorph fibrils. Free Energy Landscape (FEL) analysis highlights a shift toward more flexible and less compact conformations upon oxidation. Additionally, potential of mean force (PMF) calculations indicate that oxidation weakens inter-chain interactions, lowering the dissociation free energy and suggesting an increased propensity for fibril disassembly. Notably, oxidation disrupts key salt bridges (Glu46-Lys80, Lys45-Glu57) and the hydrophobic packing of Phe94, further contributing to structural destabilization. These findings provide molecular insights into how oxidative modifications influence αSyn polymorph fibril dynamics, reinforcing the role of oxidative stress in fibril destabilization. A more in-depth understanding of these mechanisms could inform therapeutic strategies aimed at preventing or reversing αSyn complex aggregates in neurodegenerative diseases.